Excess NF-κB induces ectopic odontogenesis in embryonic incisor epithelium - Blackburn, J; Kawasaki, K; Porntaveetus, T; Kawasaki, M; Otsuka-Tanaka, Y; Miake, Y; Ota, M S; Watanabe, M; Hishinuma, M; Nomoto, T; Oommen, S; Ghafoor, S; et al. (Journal of dental research, 2015)
Nuclear factor kappa B (NF-κB) signaling plays critical roles in many physiological and pathological processes, including regulating organogenesis. Down-regulation of NF-κB signaling during development results in hypohidrotic ectodermal dysplasia. The roles of NF-κB signaling in tooth development, however, are not fully understood. We examined mice overexpressing IKKβ, an essential component of the NF-κB pathway, under keratin 5 promoter (K5-Ikkβ). K5-Ikkβ mice showed supernumerary incisors whose formation was accompanied by up-regulation of canonical Wnt signaling. Apoptosis that is normally observed in wild-type incisor epithelium was reduced in K5-Ikkβ mice. The supernumerary incisors in K5-Ikkβ mice were found to phenocopy extra incisors in mice with mutations of Wnt inhibitor, Wise. Excess NF-κB activity thus induces an ectopic odontogenesis program that is usually suppressed under physiological conditions.
Keywords: mutace; Ameloblasts; mikroradiografie; Animals; zubní zárodek; epitel; Microradiography; apoptóza; Phenotype; zobrazování trojrozměrné; Amelogenin; Imaging, Three-Dimensional; Apoptosis; odontogeneze; Hedgehog Proteins; Odontogenesis; kostní morfogenetické proteiny; rentgenová mikrotomografie; Mice; kinasa I-kappa B; mutantní kmeny myší; Mutation; Tooth, Supernumerary; myši; zuby přespočetné; Wnt Signaling Pathway; Epithelium; Tooth Germ; Bone Morphogenetic Proteins; Incisor; I-kappa B Kinase; zubní sklovina; ameloblasty; receptory buněčného povrchu; signální dráha Wnt; Mice, Mutant Strains; řezáky; Receptors, Cell Surface; keratin-15; NF-kappa B; zvířata; fenotyp; promotorové oblasti (genetika); Dental Enamel; amelogenin; Promoter Regions, Genetic; X-Ray Microtomography; Keratin-15; proteiny hedgehog